Recent advances in aptamer discovery, modification and improving performance - Arezoo Fallah; Abbas Ali Imani Fooladi; Seyed Asghar Havaei; Mahdieh Mahboobi; Hamid Sedighian (Biochemistry and Biophysics Reports, 2024)
Aptamers are nucleic acid (Ribonucleic acid (RNA) and single strand deoxyribonucleic acid (ssDNA)) with a length of approximately 25–80 bases that can bind to particular target molecules, similar to monoclonal antibodies. Due to their many benefits, which include a long shelf life, minimal batch-to-batch variations, extremely low immunogenicity, the possibility of chemical modifications for improved stability, an extended serum half-life, and targeted delivery, they are receiving a lot of attention in a variety of clinical applications. The development of high-affinity modification approaches has attracted significant attention in aptamer applications. Stable three-dimensional aptamers that have undergone chemical modification can engage firmly with target proteins through improved non-covalent binding, potentially leading to hundreds of affinity improvements. This review demonstrates how cutting-edge methodologies for aptamer discovery are being developed to consistently and effectively construct high-performing aptamers that need less money and resources yet have a high chance of success. Also, High-affinity aptamer modification techniques were discussed.